2015
DOI: 10.1007/s13394-015-0157-8
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ teaching practices and beliefs regarding context-based tasks and their relation with students’ difficulties in solving these tasks

Abstract: In this study, we investigated teachers' teaching practices and their underlying beliefs regarding context-based tasks to find a possible explanation for students' difficulties with these tasks. The research started by surveying 27 Junior High School teachers from seven schools in Indonesia through a written questionnaire. Then, to further examine teachers' teaching practices related to context-based tasks, four teachers were observed and video recorded in two mathematics lessons in which they were asked to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Instrumental teaching practices are very identical to learning based on results rather than process, so learning that is relevant to the context of students is often ignored. These findings strengthen previous studies about the teaching practices of Indonesian mathematics teachers in class (Purnomo, Suryadi, & Darwis, 2016;Wijaya, van den Heuvel-Panhuizen, & Doorman, 2015), in which teacher practices are more dominated by traditional practices. Through class observations, Wijaya found that practices of mathematics teachers, concerning how contextbased tasks are taught, leaned more toward a directive teaching approach.…”
Section: Findings Regarding the Second Questionsupporting
confidence: 89%
See 1 more Smart Citation
“…Instrumental teaching practices are very identical to learning based on results rather than process, so learning that is relevant to the context of students is often ignored. These findings strengthen previous studies about the teaching practices of Indonesian mathematics teachers in class (Purnomo, Suryadi, & Darwis, 2016;Wijaya, van den Heuvel-Panhuizen, & Doorman, 2015), in which teacher practices are more dominated by traditional practices. Through class observations, Wijaya found that practices of mathematics teachers, concerning how contextbased tasks are taught, leaned more toward a directive teaching approach.…”
Section: Findings Regarding the Second Questionsupporting
confidence: 89%
“…In their study, Wijaya, van den Heuvel-Panhuizen, and Doorman (2015) have examined the teaching practices of junior secondary mathematics teachers by use of observations, videos, and self-reports. However, this research only focused on teaching practices related to context-based mathematics learning.…”
Section: A Introductionmentioning
confidence: 99%
“…The data about teachers' teaching practice were collected through a written questionnaire and classroom observations (see Wijaya, Van den Heuvel-Panhuizen, & Doorman, 2015b). The questionnaire focused on the characteristics of context-based tasks used by teachers in their teaching practices.…”
Section: Opportunity-to-learn Offered By Teaching Practices Of Indonementioning
confidence: 99%
“…The second dimension of opportunity-to-learn investigated in the CoMTI project was teachers' teaching practices. For this dimension Wijaya, Van den Heuvel-Panhuizen, and Doorman (2015b) found that the way teachers taught context-based tasks also did not provide sufficient opportunities for students to learn to solve context-based tasks. The teachers tended to use a directive teaching approach in which they tell the students what a context-based task is about, translate the task into a mathematical problem, and explain what mathematical procedure to carry out.…”
Section: The Context-based Mathematics Tasks Indonesia Projectmentioning
confidence: 99%